2016
DOI: 10.1111/1462-2920.13133
|View full text |Cite
|
Sign up to set email alerts
|

In situprotein‐SIP highlights Burkholderiaceae as key players degrading toluene by para ring hydroxylation in a constructed wetland model

Abstract: In constructed wetlands, organic pollutants are mainly degraded via microbial processes. Helophytes, plants that are commonly used in these systems, provide oxygen and root exudates to the rhizosphere, stimulating microbial degradation. While the treatment performance of constructed wetlands can be remarkable, a mechanistic understanding of microbial degradation processes in the rhizosphere is still limited. We investigated microbial toluene removal in a constructed wetland model system combining 16S rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 57 publications
(71 reference statements)
4
39
0
Order By: Relevance
“…Such PFR systems were further used to investigate microbial degradation of the aromatic hydrocarbon toluene by isotope fractionation and DNA microarray analysis, 16S rRNA amplicon sequencing (24), and protein-based stable isotope probing (protein-SIP) (25). These studies revealed that toluene was predominantly or even exclusively degraded aerobically by members of the Burkholderiales via a sequential monooxygenation of the aromatic ring followed by ring cleavage through an extradiol dioxygenase.…”
mentioning
confidence: 99%
“…Such PFR systems were further used to investigate microbial degradation of the aromatic hydrocarbon toluene by isotope fractionation and DNA microarray analysis, 16S rRNA amplicon sequencing (24), and protein-based stable isotope probing (protein-SIP) (25). These studies revealed that toluene was predominantly or even exclusively degraded aerobically by members of the Burkholderiales via a sequential monooxygenation of the aromatic ring followed by ring cleavage through an extradiol dioxygenase.…”
mentioning
confidence: 99%
“…Proteins corresponding to quantified mRNA were not found, however the proteomic survey was a general success. A follow up study by Lünsmann et al [41] utilized proteomics, stable isotope analysis and metagenomics to further elucidate a specific bacterial family (Burkholderiaceae) and functional pathways mainly responsible for toluene degradation in lab-scale TWs.…”
Section: Functional Assessmentmentioning
confidence: 99%
“…Stable isotope analysis was also sometimes classified as a type of activity measure. For example, Braeckevelt et al [45] used stable isotope analysis to study the degradation of monochlorobenzene, and Lünsmann et al [41] for the study of toluene degradation. It was however admittedly difficult to properly categorize these studies (and other isotope studies) within the four-category construct (activity, enumeration, function, and structure) of this meta-analysis.…”
Section: Functional Assessmentmentioning
confidence: 99%
See 2 more Smart Citations